The Perception of Primary School English Teacher with Non-English Educational Background towards Pedagogical Content Knowledge: - - Dewa Ayu Ratna Lily Pastika; I. G. A. Lokita Purnamika Utami; G. A. P. Suprianti (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
Basic skills and knowledge that must be owned by a teacher is pedagogical content knowledge. Pedagogical content knowledge is all aspects related to teaching and learning activities in class, for example lesson planning, learning design, understanding of the curriculum, assessment, and mastery of knowledge of the subject matter being taught. This study aims to analyze non-educational English teachers perceive of pedagogical content knowledge, and determine the consistency between perception and implementation. This research involved three non-educational English teachers who teach in elementary schools. The method used is embedded mix-method where qualitative data is primary data and qualitative data is secondary data. There are three instruments used in the study, including questionnaires, observation sheets, and interview guides. Based on the results of the questionnaire obtained teachers' perceptions of pedagogical content knowledge is high. Then the results of the observations show very low data. To ensure the data obtained, interviews were conducted with teachers and the results showed that there was no consistency between perception and implementation. The inconsistency between perception and implementation is caused by the teacher's limitations in developing learning designs, the various characteristics and needs of students, and the general use of English by teachers and students because English is a content subject. Therefore, the implication of this research is that teachers can use technology to access learning resources, examples of lesson plans and designs, as well as take advantage of the environment around students.